2018
DOI: 10.1111/mmi.13968
|View full text |Cite
|
Sign up to set email alerts
|

The global regulator of pathogenesis PnCon7 positively regulates Tox3 effector gene expression through direct interaction in the wheat pathogen Parastagonospora nodorum

Abstract: To investigate effector gene regulation in the wheat pathogenic fungus Parastagonospora nodorum, the promoter and expression of Tox3 was characterised through a series of complementary approaches. Promoter deletion and DNase I footprinting experiments identified a 25 bp region in the Tox3 promoter as being required for transcription. Subsequent yeast one-hybrid analysis using the DNA sequence as bait identified that interacting partner as the C2H2 zinc finger transcription factor PnCon7, a putative master regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
(63 reference statements)
2
18
0
Order By: Relevance
“…Evidence is accumulating that distinct sets of effector genes are coordinately expressed in successive waves during the course of host infection, reflecting the complexity of effector gene regulation and the diversity of TFs and cis ‐regulatory sequences (Dong et al., 2015; Farfsing et al., 2005; Gervais et al., 2017; Hacquard et al., 2013; Kleemann et al., 2012; Lanver et al., 2018; O’Connell et al, 2012; Soyer et al., 2014; Wang et al., 2011). Fungal genomes collectively contain at least 36 different families of TFs, and 13 TFs from four families are known for their roles in effector regulation (Lin et al., 2018; Tan & Oliver, 2017). M. oryzae is predicted to contain a total of 495 TFs (4.5% of the 11,054 proteins in M. oryzae ) (Park et al., 2013), and thus far MoGti1 is the only TF known to regulate the expression of M. oryzae effector genes, including PWL2 (Li et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is accumulating that distinct sets of effector genes are coordinately expressed in successive waves during the course of host infection, reflecting the complexity of effector gene regulation and the diversity of TFs and cis ‐regulatory sequences (Dong et al., 2015; Farfsing et al., 2005; Gervais et al., 2017; Hacquard et al., 2013; Kleemann et al., 2012; Lanver et al., 2018; O’Connell et al, 2012; Soyer et al., 2014; Wang et al., 2011). Fungal genomes collectively contain at least 36 different families of TFs, and 13 TFs from four families are known for their roles in effector regulation (Lin et al., 2018; Tan & Oliver, 2017). M. oryzae is predicted to contain a total of 495 TFs (4.5% of the 11,054 proteins in M. oryzae ) (Park et al., 2013), and thus far MoGti1 is the only TF known to regulate the expression of M. oryzae effector genes, including PWL2 (Li et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recently published literature has reported that multiple transcription factors are responsible for NE gene regulation. The C2H2 zinc finger transcription factors P. nodorumCon7 (PnCon7), a zinc finger transcription factor, and Stagonospora nodorum StuA, an ASM-1, Phd1, StuA, EFG1, and Sok2 domain transcription factor, have been reported to be regulators of SnTox3 (IpCho et al, 2010;Lin et al, 2018). Lin et al (2018) found through silencing of PnCon7, there was a corresponding decrease in SnTox3 expression.…”
Section: Differences In Ne Gene Promoter and Protein Sequences May Inmentioning
confidence: 99%
“…The C2H2 zinc finger transcription factors P. nodorumCon7 (PnCon7), a zinc finger transcription factor, and Stagonospora nodorum StuA, an ASM-1, Phd1, StuA, EFG1, and Sok2 domain transcription factor, have been reported to be regulators of SnTox3 (IpCho et al, 2010;Lin et al, 2018). Lin et al (2018) found through silencing of PnCon7, there was a corresponding decrease in SnTox3 expression. Although PnCon7 was found to not be directly correlated with SnTox1 expression, silencing of PnCon7 led to decreased SnTox1 and SnToxA expression.…”
Section: Differences In Ne Gene Promoter and Protein Sequences May Inmentioning
confidence: 99%
“…A gene expression analysis and cross-species functional complementation in S. cerevisiae revealed cellular adhesins and secreted enzymes were controlled by Con7 in these species (Tran et al, 2014). Although knockout mutants were not obtainable, suggesting a role in viability, gene knockdown of the P. nodorum orthologue PnCon7 revealed it regulates the expression of necrotrophic effector genes and was correlated with reduced virulence on susceptible wheat (Lin et al, 2018). Furthermore, a yeast-1-hybrid analysis indicated PnCon7 directly targeted a promoter element of the necrotrophic effector SnTox3.…”
Section: Con7: Development and Virulencementioning
confidence: 99%